Activity of Using Social Media During Pandemic: Aktivitas Penggunaan Media Sosial Dimasa Pandemi - Suryani Manurung; Dika Iftinan Munawarah; Emilia Azahra; Hanifah Suryani Putri; Ismy Adryanti; Muhammad Husein; Nur Holisoh; Olivia Oktafiana Sinaga; Puspita Arum; Sarifatun Mardiyah; Dwi Novita Ramdania (Politeknik Kesehatan Kemenkes RI Jakarta I, 2021)
Currently Social media is widely used by the public, especially during pandemic. Various information founded throughsocial media, this aims of the research to determine utility of social media during a pandemic. The research method is aquantitative study with a survey. The survey is filled out via Google From which is distributed in group chats and personalchats. The data collection time was September 27, 2021. There were 81 participants, students, and workers. Participantsdistribution of the questionnaires were conducted in DKI Jakarta, Bogor, Depok, Tangerang, and Bekasi. Researchresult; characteristics of respondents 61.71% are women with student status. Social media that is widely used is WhatsAppas much as 40.5% of is used to share information. The duration of using social media is more than 8 hours 23.5%. Thepositive impact of using social media is to add as much as 22.3% of the information. The negative impact of social mediais tired eyes as much as 37.5%. The conclusion based on survey results, activities using social media during a pandemicwere carried out by every group regardless of age and profession which had positive and negative influences. Suggestionsfrom this study are expected to study various phenomena and problems that occur so that writing is interesting and useful for readers